Health Literacy and self-management in Non-communicable diseases (NCDs) - Tongpeth, Jintana; Chowararak, Natkritta; Som-jai, Chanapa; Indhraratana, Apinya; Siriwan, Thitaporn (Journal of The Royal Thai Army Nurses, 2021)
Patients with non-communicable diseases (NCDs) are essential and crucial in modifying health behaviors to be consistent and appropriate with their illnesses by motivating them to take care of and manage their health problems. Health literacy, which is a cognitive and social skill, helps a person to reach understand and use information in different ways. This leads to the development ability and self-management skills to maintain and continued good health. Nurses and health care personnel team as a conssequence play an important role in promoting and supporting NCDs patients to manage themselves by using Health Literacy to control their diseases as well as decrease the severity and complications of the illness, promote quality of life resulting in reduced healthcare costs. This academic article accordingly presents the concept of health literacy and the sequence of steps for developing health literacy in the context of Thailand as well as presenting concepts and self-management processes of individuals and families including bringing such concepts into practice so that it can be applied in the development of supporting intervention, promote self-management in combination with the development of health literacy in patients with NCDs. This is the key to success and further improving health outcomes in patients with NCDs.